Motivasi Belajar Siswa dalam Pendidikan Jasmani Olahraga dan Kesehatan Kelas XI SMK Bina Karya 1 Karawang di masa Pandemi - Muhamad Syafei; Abduloh Abduloh; Nana Suryana Nasution (Peneliti.net, 2021)
The purpose of this study was to determine the level of student motivation and learning outcomes of Vocational School Bina Karya 1 Karawsang students during the Covid-19 pandemic which was carried out remotely or online. This research is descriptive qualitative research. The research subjects were teachers of Physical Education studies and students of class XI Vocational School Bina Karya 1 Karawang, the data collection methods used were observation, interviews (interviews), and documentation. Based on the results of the research, the level of student learning motivation during the Covid-19 pandemic decreased due to several factors that influenced the decline in student learning motivation, internal factors, external factors, environmental factors, learning method factors, these factors were related. If there are no factors, the learning process will not be effective. Teachers play an important role in the decline in student motivation, teachers must continue to encourage students to awaken student learning motivation. The decline in student learning outcomes is influenced by a low level of motivation, so if student learning motivation is low, learning outcomes will also decrease, learning media is a factor in decreasing student learning outcomes if there are no learning media it will hinder the learning process so that it affects student learning outcomes.